Empowering Indonesian Migrant Workers Through Financial Literacy and Entrepreneurship - Mahfirah, Titis Fatarina; Fauzi, Achmad; Widyastuti, Umi; Muliasari, Indah; Hidayat, Nurdin; Armeliza, Diah; Lajuni, Nelson; Zahro, Khalisatuz; Ferrari; Yasmin, Eka Faradila (Rahmatan Lil 'Alamin Journal of Community Services, 2024)
Financial literacy has emerged as a critical aspect of economic empowerment, yet significant disparities persist between countries. According to the 2019 Household, Income and Labour Dynamics in Australia (HILDA) survey, Australia boasts a financial literacy rate of 64%, while Indonesia lags behind at only 38% (Australia Indonesia Youth Association, 2020). Recognizing this gap, this initiative aims to address the financial literacy needs of Indonesian migrant workers through targeted training programs. Drawing on data from the 2022 National Survey on Financial Literacy and Financial Inclusion (Survei Nasional Literasi dan Inklusi Keuangan/SNLIK), which showed an increase to 49.68% in Indonesia (Otoritas Jasa Keuangan, 2022), our community outreach initiative focuses on raising awareness and providing practical knowledge on entrepreneurship among migrant workers. By offering workshops on International Community Outreach with the theme "Raising Entrepreneurial Success Among Indonesian Migrant Workers," this activity aims to equip participants with the skills and inspiration to start their businesses upon returning to Indonesia. Through training sessions on budget management and entrepreneurship, we strive to empower migrant workers to achieve financial independence and contribute to their personal economic well-being. This initiative embodies our commitment to fostering self-sufficiency and economic resilience among Indonesian migrant workers.